Systematics and Phylogeny of Ulmeritus-Ulmeritoides revisited (Ephemeroptera: Leptophlebiidae) - Salles, F. F.; Domínguez, E. (Zootaxa, 2012)
Based on specimens recently collected from Brazil, two new species of Ulmeritoides, as well as the nymph and female imago of the atypical U. flavopedes are described. A new synonymy is proposed, U. flavopedes (=U. oepa). In order to re-evaluate the relationships of the species of the Ulmeritus-Ulmeritoides group based on these new evidences, a cladistic analysis is carried out. The monophyly of Ulmeritus and Ulmeritoides is reconfirmed, and a clear differentiation between the Central and South American species of Ulmeritoides emerges from the analysis.